1996
DOI: 10.1023/a:1016021115481
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The anionic buffer species and not the pH had a significant effect on the hydration and hence on the drug release from beads coated with the cationic polymers, Eudragit RS and RL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Buffer species-dependent drug release kinetics of diltiazem from Eudragit RS/RL-coated beads has been reported. Due to the different strength of interaction between the buffer anions and the quaternary ammonium groups of Eudragit RS/RL, the order of drug release in various buffer media was found as follows: acetate > formate > chloride [99]. To achieve a sigmoidal drug release profile, a bead system has been prepared by coating Eudragit RS onto a drug core containing drug and organic acid ( Figure 1B ) [100,101].…”
Section: Ion-sensitive Polymersmentioning
confidence: 99%
“…Buffer species-dependent drug release kinetics of diltiazem from Eudragit RS/RL-coated beads has been reported. Due to the different strength of interaction between the buffer anions and the quaternary ammonium groups of Eudragit RS/RL, the order of drug release in various buffer media was found as follows: acetate > formate > chloride [99]. To achieve a sigmoidal drug release profile, a bead system has been prepared by coating Eudragit RS onto a drug core containing drug and organic acid ( Figure 1B ) [100,101].…”
Section: Ion-sensitive Polymersmentioning
confidence: 99%
“…Several researchers have studied the effects of plasticizers when used with various grades of Eudragits (3,5,(11)(12)(13)(14)(15)(16). Dyer and coworkers evaluated, in part, the effect of plasticizers on drug release from film-coated pellets (16).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, drug release from the polymer matrix depends on the exchange between the anions dissolved in the dissolution media and the quaternary ammonium groups of polymer (Wagner & McGinity, 2002 ). Since the dissolution media at pH 1.2 had chloride anions which are less selective to ion exchange than phosphate ion at pH 6.8, the degree of hydration and permeability of polymer matrix decrease at acidic condition (Bodmeier et al., 1996 ; Wagner & McGinity, 2002 ). Some of previous studies also reported that drug release rates from pellets coated with ammonio methacrylate copolymers varies in the dissolution media containing different anions (Knop, 1996 ; Wagner & McGinity, 2002 ).…”
Section: Resultsmentioning
confidence: 99%